The Global, Regional and Local Politics of Institutional Responses to COVID-19 Implications for Women and Children - Hosli, Madeleine O.; Blessing, Amy.; Iacovidou, Irini (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
The shift from response to recovery is now noticeable as the world moves past the paralyzing effects of the COVID-19 pandemic. This book explores responses to the pandemic by international, regional, and local institutions, multilateral action, and crisis prevention efforts at different levels of governance, with a specific focus on the situation of women and children. The contributions in this volume address novel topics and expand the analysis to the different challenges faced by women and children, linking these to the Sustainable Development Goals, to create a holistic view of the true impact of the pandemic. The focus on international and regional cooperation provides further insights on how management of the COVID-19-induced crisis can be altered and improved. Immediate effects of the pandemic were focused on healthcare, but long-term and knock-on effects spread to different societal sectors and must be analyzed to ensure they will be addressed and, ultimately, resolved. Madeleine O. Hosli is Professor of International Relations at Leiden University, The Netherlands. She is author of The European Union and the United Nations in Global Governance (2022) and co-editor of The Changing Global Order (2020) and The Future of Multilateralism: Global Cooperation and International Organization (2021). Amy Blessing is an initiative coordinator at the Global Counterterrorism Forum (GCTF) Administrative Unit based at T.M.C. Asser Institute, The Hague, and treasurer at Women in International Security Netherlands. She previously worked at Leiden University as a program coordinator and has LLMs from the University of Glasgow and University of Copenhagen. Irini Iacovidou is a project coordinator at Perrett Laver, The Netherlands. She has an MSc from Leiden University in International Relations and Diplomacy. Her current research interests focus on multilateralism and international cooperation, particularly the EU's position vis-à-vis its neighboring states. .
1. Introduction, Amy Blessing, Irini Iacovidou -- 2. Leaving No One Behind: Development Financial Insitutions and Gender Lens Investing in Sub-Saharan Africa , Amy Blessing) -- 3. Women and Children: International Institutions and Responses to Covid-19, Madeleine O. Hosli -- 4. Eradicating Child Labour amids Global Crises, Moona Hoppula -- 5. Crisis Management in Southeast Asia: Women, Violent Extremism and Covid-19, Aude Gregory-Billet -- 6. Preventing a Knock-On Pandemic: How the World's Biggest Children's Charity Responded to the Virus that Doesn't Make Children Sick, Chiara Orlassino -- 7. Falling through the Cracks: Challenges to the Education of Refugee Children during Covid-19, Anna Saischek -- 8. Covid-19 and the Digital Divide: Responding to the South Asian Digital Divide in the Education Sector, Irini Iacovidou, Himanshi Sharma -- 9. Increased Domestic Violence in Europe: A Shadow Pandemic, Solene Zumsteeg -- 10. School's Out Forever? The Effect of COVID-19 on Educational Opportunities for Women and Girls in the Global South, Alanna O'Malley -- 11. Women's Empowerment: Analyzing Ethiopia's Amhara National Regional State, Tesfanesh Tadesse, Abebech Chekol, Taglo Layew, Walelign Awoke -- 12. COVID-19 in the Americas: Challenges in the Institutionalisation of the Gender Equality Agenda, Gabriela Meneghetti Godinho Bueno and Luiza Martins Santos -- 13. Conclusion, Amy Blessing and Irini Iacovidou.
Keywords: International organization; Political science; International relations; International Organization; Governance and Government; International Relations